Amphibi House Sebagai Mitigasi Banjir Rob di Daerah Pesisir Belawan Bagan Deli - Novalinda Novalinda; Rahmadhani Fitri; Benny Iskandar; Amelin Al Yunirsyah; Erisliana Utari (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
Generally, tidal flooding that comes every day to belawan Bagan Deli beach is a serious problem. Many of the causes of this tidal flood include global warming, seawater at high tide, and poor drainage due to the large piles of garbage. The tide level reached 2.7 meters from the current sea level, and people's economic activities stopped for a while. The pile of garbage caused the surrounding houses to become shabby and dirty. This study aims to obtain a home design solution in anticipation of high tide due to tidal flooding that enters residents' homes with the concept of floating houses in the Bagan Deli area. The research method uses the floating foundation engineering design method by using a floating system on the foundation (base) of the house and the connection on the pole so that the house remains in place (fixed position). The results of this study will be conveyed back to the community and local government to improve the quality of life of the people in the Bagan Deli Belawan area.